2020
DOI: 10.1021/acs.inorgchem.9b03647
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chain Initiation Efficiency in the Cationic Allyl-Nickel Catalyzed (Co)Polymerization of Ethylene and Methyl Acrylate

Abstract: Improving the efficiency of chain initiation is highly important and also highly challenging in the development of olefin polymerization catalysts. A series of 2-methylallyl-based nickel complexes supported by aryl-N-bridged diphosphazane monoxide (PNPO) ligands containing different electronic and steric substituents were prepared and characterized. These nickel complexes are highly active single-component catalysts for ethylene polymerization and copolymerization with methyl acrylate (MA). 2-Methylallyl subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…In the field of polyolefin research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], many studies have reported on the homopolymerization of ethylene [ 21 , 22 , 23 , 24 ], different higher 1-alkene [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and linear internal alkenes [ 32 , 33 , 34 ] using Brookhart-type α-diimine nickel and palladium catalysts [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ] because of the chain-walking process [ 42 , 43 , 44 , 45 ]. The interest in highly branched polyolefins such as dendrimer and hyper branched polymers has increased obviously in recent years owing to these unique physical properties, chemical properties, and their potential applications as adhesives, lubricants, and paints [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of polyolefin research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], many studies have reported on the homopolymerization of ethylene [ 21 , 22 , 23 , 24 ], different higher 1-alkene [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and linear internal alkenes [ 32 , 33 , 34 ] using Brookhart-type α-diimine nickel and palladium catalysts [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ] because of the chain-walking process [ 42 , 43 , 44 , 45 ]. The interest in highly branched polyolefins such as dendrimer and hyper branched polymers has increased obviously in recent years owing to these unique physical properties, chemical properties, and their potential applications as adhesives, lubricants, and paints [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mononuclear nickel and palladium catalysts were used in this type of polymerization and showed diverse catalytic activity against polar monomers [5,11–16] . Mostly, these structures were based on α‐diimine ligands used for copolymerization of α‐olefin with polar monomers [17–23] .…”
Section: Introductionmentioning
confidence: 99%
“…Polyolefins have been the world's largest produced synthetic polymers [1]. Late-transition-metal catalysts can mediate olefin copolymerization with polar monomers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], providing a direct and potentially economic way to access functionalized polyolefins with some improved properties as well as some unique functions [22][23][24][25][26][27][28][29][30][31]. In the 1990s, Brookhart et al reported the studies of α-diimine Pd catalysts for olefin polymerization and copolymerization with polar monomers (Chart 1A) [32][33][34].…”
Section: Introductionmentioning
confidence: 99%